PHYSICOCHEMICAL AND SENSORY CHARACTERISTICS OF CRYSTAL GUAVA (PSIDIUM GUAJAVA L.) SYRUP - Hutami, Rosy (Jurnal Pertanian, 2020)
Food diversification based on crystal guava fruit is still limited. The purpose of this study were to utilize crystal guava fruit in the form of processed syrup and to determine the effect of ratio of the guava flesh vs water and sugar concentration to the characteristic of crystal guava syrup. The experimental design that used in this study was a Completely Randomized Design (CRD) with two factors. The first factor was the ratio of guava flesh and water which consist of three levels, namely A1 (30:70), A2 (40:60), A3 (50:50) and the second factor was sugar concentration that was also consist of three levels, namely B1 (50%), B2 (60%), B3 (70%). Product analysis included chemical test (total sugar), physical test (viscosity and total dissolved solids), microbial analysis (total plate count) and sensory  test (quality and hedonic test) of selected crystal guava syrup. Statistical analysis was done by using ANOVA with Duncan. The selected crystal guava syrup was the ratio of guava flesh and water 50:50 and sugar concentration 70%. It had total sugar, viscosity and total dissolved solid (TDS) about 75,11%, 9,92cP and 77,70◦brix, respectively. Selected guava syrup was tested for total plate count and the result obtained was 7,7x101 CFU/mL that had conformed to SNI 3544:2013. The result of sensory quality of the selected product was the color leads to yellowish white, the aroma leads to the smell of crystal guava, the taste leads to sweet acidity, and the flavor leads to crystal guava with the result of hedonic test was leads towards likes (6.07-6, 89).